2008
DOI: 10.1007/s10935-008-0139-7
|View full text |Cite|
|
Sign up to set email alerts
|

Every Family: A Population Approach to Reducing Behavioral and Emotional Problems in Children Making the Transition to School

Abstract: A large-scale population trial using the Triple P-Positive Parenting Program (TPS) was evaluated. The target population was all parents of 4- to 7-year-old children residing in ten geographical catchment areas in Brisbane (intervention communities) and ten sociodemographically matched catchment areas from Sydney (5) and Melbourne (5), care as usual (CAU) comparison communities. All five levels of the Triple P multilevel system of intervention were employed; including a local mass media strategy, a primary care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
129
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(136 citation statements)
references
References 34 publications
1
129
0
6
Order By: Relevance
“…Um eine hohe Qualität der elternbezogenen Interventionen zu garantieren, wird ein universitär verankertes, interdisziplinäres Ausbildungs-und Lizensierungssystem für erforderlich gehalten, wie es etwa in Australien bereits für Fachkräte aus Medizin, Psychologie, Erziehung und Sozialarbeit geschafen wurde (Sanders et al, 2004a(Sanders et al, , 2008 und im deutschsprachigen Raum bereits für das Elternprogramm StandardTripleP umgesetzt worden ist (Heinrichs, 2006a Die Kritik an der Auszeit-Komponente des SSTP richtet sich (a) auf die Verwendung einer aversiven Maßnahme in einem Programm für behinderte Menschen als solche (Wiese et al, 2005); (b) auf den Mangel an strengen Indikationskriterien, den Einsatz von Auszeitstrategien bei Problemen, die nicht erkennbar gravierend sind sowie die Nichtbeachtung von möglichen schädlichen Nebenwirkungen (Probst u. Spreitz, 2008); (d) auf die zu geringe Berücksichtigung behinderungsspeziischer Bedingungshintergründe des Problemverhaltens (Eltern Fokus-Gruppe von Kindern mit autistischen Störungen, Whittingham et al, 2006).…”
Section: Methodenunclassified
See 1 more Smart Citation
“…Um eine hohe Qualität der elternbezogenen Interventionen zu garantieren, wird ein universitär verankertes, interdisziplinäres Ausbildungs-und Lizensierungssystem für erforderlich gehalten, wie es etwa in Australien bereits für Fachkräte aus Medizin, Psychologie, Erziehung und Sozialarbeit geschafen wurde (Sanders et al, 2004a(Sanders et al, , 2008 und im deutschsprachigen Raum bereits für das Elternprogramm StandardTripleP umgesetzt worden ist (Heinrichs, 2006a Die Kritik an der Auszeit-Komponente des SSTP richtet sich (a) auf die Verwendung einer aversiven Maßnahme in einem Programm für behinderte Menschen als solche (Wiese et al, 2005); (b) auf den Mangel an strengen Indikationskriterien, den Einsatz von Auszeitstrategien bei Problemen, die nicht erkennbar gravierend sind sowie die Nichtbeachtung von möglichen schädlichen Nebenwirkungen (Probst u. Spreitz, 2008); (d) auf die zu geringe Berücksichtigung behinderungsspeziischer Bedingungshintergründe des Problemverhaltens (Eltern Fokus-Gruppe von Kindern mit autistischen Störungen, Whittingham et al, 2006).…”
Section: Methodenunclassified
“…Diese bisherigen positiven Befunde sind weitgehend konsistent mit den Ergebnissen mehrerer Evaluationsstudien zur internen Validität des Standard-Triple-P-Programms (Sanders, 2008). Als einschränkende Faktoren der internen Validität sind anzuführen: (a) ausstehende Untersuchungen an diagnostischen Subgruppen innerhalb der diagnostischen Schirm-Kategorie "Entwicklungsbehinderungen" (b) die noch mit Unsicherheit behateten Schätzungen der Outcome-Efektstärken auf Basis der Evaluationsstudien-Stichprobe von n = 2 sowie der moderaten Probanden-Stichprobengrößen (c) ausstehende Replikationsstudien aus dem deutschsprachigen Raum; (d) Mangel an Efektivitätsstudien außerhalb der Forscher-Community um M. R. Sanders.…”
Section: Zusammenschau Der Ergebnisse Zur Validität Des Sstp-programmsunclassified
“…Only three studies examined child abuse outcomes specifically and found a reduction in the incidence of abusive head injuries [49], child maltreatment injuries [56] and child maltreatment cases [52,56]; though one was not statistically significant [52]. However, some measure of behavior change was assessed in more than half (58.8%) of the studies [46,47,[49][50][51][52][53][56][57][58][59]. Significant decreases were seen in child behavior problems [47,[57][58][59] and in dysfunctional or coercive parenting behaviors [47,51,57,59].…”
Section: Outcome Evaluationmentioning
confidence: 99%
“…However, some measure of behavior change was assessed in more than half (58.8%) of the studies [46,47,[49][50][51][52][53][56][57][58][59]. Significant decreases were seen in child behavior problems [47,[57][58][59] and in dysfunctional or coercive parenting behaviors [47,51,57,59]. Two studies reported increases in calls to helplines to report child abuse cases [46,52].…”
Section: Outcome Evaluationmentioning
confidence: 99%
“…The most comprehensive meta-analysis conducted to date (Sanders, Kirby, et al, 2014) revealed significant short-and long-term improvements for children's social, emotional and behavioural outcomes (medium effect), parenting practices (medium effect), parenting satisfaction and efficacy (medium effect), parental adjustment (small-medium effect) and parental relationship (small effect). Several studies have also investigated the effects of Triple P as a public-health intervention and recorded significant population-level impact across a range of outcomes including behavioural and emotional problems in children, parent-child relationship, coercive parenting, and parental depression and stress (Fives, Pursell, Heary, Nic Gabhainn, & Canavan, 2014;Sanders et al, 2008;Sarkadi, Sampaio, Kelly, & Feldman, 2014), as well as reduced incidence of child abuse, and hospitalisations, injuries and outof-home placements due to maltreatment (Prinz, Sanders, Shapiro, Whitaker, & Lutzker, 2009). …”
Section: Triple P As An Example Of a Public Health Approachmentioning
confidence: 99%